Fieldwork in teaching Geography and History: formative experiences in Brazil and Chile - Fernandes, Silvia Aparecida de Sousa [UNESP]; Silva, Osvaldo Miguel Sepulveda [UNESP] (Univ Fed Goias, Inst Estudos Socio-ambientais, 2024)
This article presents two experiences of innovation in primary and secondary education, with the aim of discussing the importance of fieldwork or study visits in the teaching of Geography and History. The innovation consists of incorporating the fieldwork technique in different educational contexts with the aim of allowing students to understand, from a critical perspective, the local reality and act towards its transformation based on problematizing the surroundings, with the aim of building and developing democratic education and citizenship training. The experiments were carried out in different projects, in Brazil and Chile. To cover the presentation of experiences, we first address spatial thinking in the curriculum and fieldwork as a methodological strategy in Geography and History. The specific practices and curricula of each of the schools are presented below. Finally, in the final considerations, we point out the similarities and differences between practices and the importance of initial teacher training and school organization so that Fieldwork, as a methodological tool, can be carried out.
Keywords: Teaching practice; Primary School; Secondary school; Chile; Brazil